Hubungan Konsep Diri Dengan Koping Spiritual Pada Pasien Kanker Payudara - Yumni, Fathiya Lutfil; Supatmi , Supatmi; Islamiyah, Ngafifatul (Universitas Muhammadiyah Surabaya, 2021)
Background: Breast cancer can affect various aspects of human life, including physiological, psychological and social aspects of sufferers. This condition triggers a decline in self-concept caused by the illness he is suffering from. So the need for coping is to overcome it with spiritual coping, the patient can more easily know God and understand his condition. Objective: To determine the relationship between self-concept and spiritual coping in breast cancer patients at the North Surabaya Regional Health Center. Method: This research design is quantitative with a cross-sectional approach with a population correlation approach with a simple random sampling technique. The research sample was 43 respondents. The questionnaire uses the Tennessee Self Concept Scale (TSCS) questionnaire for the self-concept variable and uses the Religious Spiritual Coping (Brief RCOPE) questionnaire for the spiritual coping variable. Data Analysis: using spearman rank with a significance level of 0.002. Results: The results of the study showed that 28 respondents (65.1%) had a negative self-concept and 15 respondents (34.9%) had a positive self-concept, 24 respondents (55.8%) had a positive spiritual coping and 19 respondents had a negative self-concept. (44.2%). Discussion: A negative self-concept will influence negative spiritual coping and vice versa